Entrepreneurship education, a challenging learning process towards entrepreneurial competence in education - Heliona Miço; Jonida Cungu (Administrative Sciences, 2023)
Entrepreneurship education is a recent field in education. From a field mainly related to small business, it is extended towards enhancement of students' entrepreneurial attitudes and skills. It can support students in developing an independent and versatile way by growing the spirit of entrepreneurship. Developing entrepreneurship competence among students requires the mastery of concepts by teachers. Training teachers in entrepreneurship education helps them apply specific competences, methods, and tools to encourage confidence in learners' own capabilities and to stimulate flexibility, leadership, and initiative. To understand the teachers' entrepreneurial competence, an online survey was developed to assess the level of mastery of such competence in Albanian teachers. The survey was designed to analyze the development of entrepreneurial competence of teachers, and their entrepreneurship education and training. The research goal of the survey is to evaluate the influence mechanisms of gaining entrepreneurship education competence and the way of implementing this competence in pre-university education schools. Results from the questionnaire highlighted the teachers' need for the acquisition of entrepreneurial competence at every professional level, starting from initial teacher education. The findings from the survey are analyzed by taking into consideration the European policies regarding entrepreneurship education, such as the European Entrepreneurship Competence Framework (EntreComp), and their implementation in the Albanian educational sector.
Keywords: 350; Albania; competences; EntreComp framework; entrepreneurship education; learning; teachers; university